2020
DOI: 10.3390/educsci10020036
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Characteristics of Explanations with Element Maps

Abstract: What are the structural characteristics of written scientific explanations that make them good? This is often difficult to measure. One approach to describing and analyzing structures is to employ network theory. With this research, we aim to describe the elementary structure of written explanations, their qualities, and the differences between those made by experts and students. We do this by converting written explanations into networks called element maps and measure their characteristics: size, the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…For example, Bruun et al (2019) applied semantic networks to analyse annotated speech as text to characterise the whole content of the discussion. This approach adopts the same techniques used in the network analysis of textbooks (Yun & Park, 2018) and students' written answers (Wagner et al, 2020). Similar, but distinct from semantic networks, are conceptual networks that study subject-specific concepts found in texts or utterances (Caballero et al 2020) or in concepts maps (Koponen & Nousiainen, 2019).…”
Section: Network Analysis In Science Education Researchmentioning
confidence: 99%
“…For example, Bruun et al (2019) applied semantic networks to analyse annotated speech as text to characterise the whole content of the discussion. This approach adopts the same techniques used in the network analysis of textbooks (Yun & Park, 2018) and students' written answers (Wagner et al, 2020). Similar, but distinct from semantic networks, are conceptual networks that study subject-specific concepts found in texts or utterances (Caballero et al 2020) or in concepts maps (Koponen & Nousiainen, 2019).…”
Section: Network Analysis In Science Education Researchmentioning
confidence: 99%